Lacan’s three orders, the graphe complet and music in film: - Zelda Potgieter (Communicare, 2022)
This article engages with the Lacanian tradition of film theory in order to suggest some of the ways in which music in film may be understood to contribute significantly to subject identification in filmic experience. Two points are argued: 1) that Lacan’s distinction between the three orders - the Real, the Imaginary and the Symbolic - may usefully be understood in musical terms, and, 2) that the two vectors of Lacan’s graphe complet – the vector of speech and the vector of drive – provide meaningful insight into the manner in which the three orders shape filmic musical experience. Analysis of Miklos Rosza’s score for Alfred Hitchcock’s Spellbound (1945) serves to illustrate such insights.